Excellent leukemia control after second hematopoietic cell transplants with unrelated cord blood grafts for post-transplant relapse in pediatric patients - Troullioud Lucas, Alexandre G.; Boelens, Jaap Jan; Prockop, Susan E.; Curran, Kevin J.; Bresters, Dorine; Kollen, Wouter; Versluys, Birgitta; Bierings, Marc B.; Archer, Anne; Davis, Eric; Klein, Elizabeth; Kernan, Nancy A.; et al. (Frontiers in Oncology, 2023)
Background: Patients with leukemia relapse after allogeneic hematopoietic cell transplant (HCT) have poor survival due to toxicity and disease progression. A second HCT often offers the only curative treatment.We retrospectively reviewed our bi-institutional experience (MSKCC-USA; Utrecht-NL) with unrelated cord blood transplantation (CBT) for treatment of post-transplant relapse. Overall survival (OS) and Event-Free Survival (EFS) were evaluated using the Kaplan-Meier method, treatment-related mortality (TRM) and relapse were evaluated using the competing risk method by Fine-Gray.Results: Twenty-six patients age < 21 years received a second (n=24) or third (n=2) HCT with CB grafts during the period 2009-2021. Median age at first HCT (HCT1) was 11.5 (range: 0.9-17.7) years and all patients received myeloablative cytoreduction. Median time from HCT1 to relapse was 12.8 (range 5.5-189) months.